Selected aspects of institutional early childhood education and care in Warsaw – the perspective of professionals and low-income parents - Małgorzata Karwowska-Struczyk; Olga Wysłowska (Problemy Wczesnej Edukacji)
The article presents results of research into low income parents as well as professionals involved in the education, care and upbringing sectors. It concerns access to toddler care and preschool, the costs of sending children to such institutions, support for parents on low incomes, as well as the demands parents have of these institutions. The authors carried out two group interviews with parents, as well as three individual interviews with workers from the institutions. In the final part of the article, the results of the research are presented along with recommendations for politics concerning the sectors of education, upbringing and care of children from the ages of 0 to 6.